Consumer’s Perception towards Website Factors for Online Shopping and its Effect on Buying Behavior in Peshawar (Journal of Social Sciences Review, 2023)
The use of e-commerce is growing so rapidly around the globe and provides e-marketers with many emerging opportunities. Ife-marketers get awareness about those elements and aspects which can affect consumers’ buying behavior and the relationships between these factors. Then they can further develop their marketing strategies to convert potential customers into active ones and hold current online customers. The increasing use of the Internet by Pakistani customers provides developing prospects for online retailers. This paper focuses on factors that online Peshawari buyers keep in mind while buying online. This study found that website design, website reliability/fulfillment, website customer service, and website security/privacy are the four dominant factors that influence consumer perceptions of online purchasing. Online buyers have positive evaluations of website design and website reliability/fulfillment but negative evaluations of website security/privacy issues, which implies that security/privacy issues are important to most online buyers.  Finally, the recommendations presented in this research may help foster the growth of Pakistani online marketing in the future.
Keywords: Online Shopping Behaviors; Website Design; Website Reliability; Website Customer Service; Website Privacy